Histone deacetylase inhibitors as potential therapeutic approaches for chordoma: An immunohistochemical and functional analysis. Issue 12 (24th July 2013) - Scheipl, Susanne; Lohberger, Birgit; Rinner, Beate; Froehlich, Elke Verena; Beham, Alfred; Quehenberger, Franz; Lazáry, Aron; Pal Varga, Peter; Haybaeck, Johannes; Leithner, Andreas; Liegl, Bernadette
ABSTRACT: Chordomas are rare malignancies of the axial skeleton. Therapy is mainly restricted to surgery. This study investigates histone deacetylase (HDAC) inhibitors as potential therapeutics for chordomas. Immunohistochemistry (IHC) was performed using the HDAC 1–6 antibodies on 50 chordoma samples (34 primary tumors, 16 recurrences) from 44 patients (27 male, 17 female). Pan‐HDAC‐inhibitors Vorinostat (SAHA), Panobinostat (LBH‐589), and Belinostat (PXD101) were tested for their efficacy in the chordoma cell line MUG‐Chor1 via Western blot, cell cycle analysis, caspase 3/7 activity (MUG‐Chor1, UCh‐1), cleaved caspase‐3, and PARP cleavage. p ‐Values below 0.05 were considered significant. IHC was negative for HDAC1, positive for HDAC2 in most ( n  = 36; 72%), and for HDACs 3–6 in all specimens available ( n  = 43; 86%). HDAC6 expression was strongest. SAHA and LBH‐589, but not PXD101 caused a significant increase of G2/M phase cells and of cleaved caspase‐3 ( p  = 0.0003, and p  = 0.0014 after 72 h, respectively), and a peak of caspase 3/7 activity. PARP cleavage confirmed apoptosis. The presented chordoma series expressed HDACs 2–6 with strongest expression of HDAC6. SAHA and LBH‐589 significantly increased apoptosis and changed cell cycle distribution in vitro. HDAC‐inhibitors should be further evaluated as therapeutic options for chordoma. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1999–2005, 2013